2021
DOI: 10.1080/08974438.2020.1860857
|View full text |Cite
|
Sign up to set email alerts
|

Brands, Labels, and Product Longevity: The Case of Salmon in UK Grocery Retailing

Abstract: In recent years, the number of ecolabels and country-of-origin labels has grown substantially in seafood markets globally. This makes it more difficult for retailers and producers to communicate and demonstrate their differentiating claims to consumers. In addition, it has recently been suggested that there are both costs and supply chain benefits associated with labeling. This paper uses duration analysis to investigate factors that influence product longevity for salmon in grocery retailing. Product longevit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…In the UK, premiums for MSC-labeled fish were found to be highest for discount retailers, while no premium was identified for ecolabeled fish sold at high-end retailers (e.g., Marks & Spencer, Waitrose) (Asche et al, 2015). Moreover, different chains have been shown to employ diverse strategies with respect to how ecolabels are used (Sogn-Grundvåg et al, 2019;Asche et al, 2021). To account for this, we also estimate the model with interaction terms between retailer and the ASC label.…”
Section: Empirical Modelmentioning
confidence: 99%
“…In the UK, premiums for MSC-labeled fish were found to be highest for discount retailers, while no premium was identified for ecolabeled fish sold at high-end retailers (e.g., Marks & Spencer, Waitrose) (Asche et al, 2015). Moreover, different chains have been shown to employ diverse strategies with respect to how ecolabels are used (Sogn-Grundvåg et al, 2019;Asche et al, 2021). To account for this, we also estimate the model with interaction terms between retailer and the ASC label.…”
Section: Empirical Modelmentioning
confidence: 99%
“…Therefore, wild and farmed fish brands competed fairly in the market. In contrast, Asche et al (2021) showed that farmed salmon products with local country of origin labels and ecolabels indicated a shorter life cycle than those with foreign origin labels. The difference between these findings can be attributed to the fact that different retail chains vary in labelling brands.…”
Section: Fish Farming Challenges In the Ukmentioning
confidence: 81%